Exploring political participation of Malay first-time voters and the Tiktok role in Malaysia - Ling, Sze Huey (2023)
The emergence of Internet has permeated in almost every part of our lives, and the younger generations especially are the one been permeated at most. Especially in political aspect, the emergence of social media has brought the opportunity to change the way of people to experience the politics, information seeking and involved in some political activities. Furthermore, previous studies also found out the positive relationship between social media and political participation of the youth in Malaysia. However, previous studies only focus on the social media such as Facebook, Instagram, Twitter. The new and rapidly grow social media – TikTok have not been studied before in Malaysia regarding the political participation of youth in Malaysia. Moreover, previous GE15 has been reported that TikTok is the effective and efficient tool to reach the young voters, especially the Malay first-time voters that utilized by PN and PAS. So, this study is aimed to investigate about the role of TikTok on the political participation of the first-time voters from UiTM Malaysia. A survey questionnaire has been distributed to the UiTM Malay students using snowball sampling method and collected total of 196 survey result for further data analysis and discussions. Survey results indicates that three independent variables – TikTok Usage, Political Interest and Political Knowledge have positive significant relationship with the dependent variable – Political Participations. The analysis shown political interest is the core motivation driven the UiTM Malay students for political participation during GE15. TikTok played a significant role in here, because most of the respondents agreed that they rely on TikTok for political information consumption during GE15, and the younger first-time voters will use TikTok more frequent than the other age categories. Even though result indicates that the UiTM Malay students have medium high level of political knowledge, but researcher also found out their political knowledge is limited to certain extent, which they will only obtain the political knowledge and information that related with the political parties, coalition, or candidates that they interested with, and mostly are related with PN. All the research questions and research hypotheses has been answered and accepted in the results and discussion part.